Study of the dynamics of preparedness indicators for highly skilled kayakers during the training process - Pogrebnoy, A.I.; Makarova, G.A.; Karpov, A.A.; Komlev, I.O. (Theory and Practice of Physical Culture, 2025)
Objective of the study is to identify the dynamics of technical and physical fitness indicators of highly skilled kayakers when performing various training loads during the preparatory period. Methods and structure of the study. The work utilised methods of modelling, testing, analysis of planning documents, and mathematical statistics. The following indicators were measured: time taken to cover a distance of 2000 m (time, average rowing speed) and a distance of 2×250 m (average time, speed, stroke length and technical coefficient), bench press and deadlift with a 40 kg barbell in 2 minutes. Two groups (7 people in each) of highly qualified kayakers (Honoured Master of Sports of Russia, Master of Sports of Russia of international class, Master of Sports of Russia) were monitored as they trained according to 2 different plans during the preparatory period (October-December). Testing was conducted monthly. Results and conclusions. The content of training loads and the dynamics of technical and physical fitness indicators of highly skilled kayakers training according to different plans are shown. The assessment of the average group indicators of technical and physical fitness of rowers does not allow us to identify the nature of the influence of various training loads. The improvement in the time taken to complete the test distance by all rowers in both groups is the result of the implementation of the training loads under consideration, which initiate different changes in fitness indicators, which even within each group show individual characteristics of adaptive adjustments. For rowers of high skill level, it is advisable to consider the individual dynamics of fitness indicators in relation to training load.